Evidence-Based Strategies Identified to Increase Access to Oral Health Services to Promote a Healthier Lifestyle - Breyana Davis; Sara Plaspohl (Georgia Southern University, 2016)
Background: Leading Health Indicators (LHI) are a subset of Healthy People 2020 objectives, selected to communicate at- risk health issues and actions that can be taken to address them. The number of children, adolescents, and adults who visited the dentist in the past year has decreased nationally, suggesting that oral health continues to be a problem caused by barriers preventing access to oral services. Methods: Preliminary research was conducted on the LHI via the Healthy People 2020 website. Health-related peer reviewed articles were selected and reviewed. Results: Evidenced-based literature shows that economic, educational, and personal barriers prevent access to oral services. However, through health promotion and new intervention methods, good oral health can be established. Conclusions: Primary prevention leads to improved oral health status; thus, such methods can be useful in moving the LHI objective towards the Healthy People 2020 target goal.